2016
DOI: 10.1088/0031-9155/61/13/4826
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical deformable image registration of longitudinal lung CT images using vessel information

Abstract: Spatial correlation of lung tissue across longitudinal images, as the patient responds to treatment, is a critical step in adaptive radiotherapy. The goal of this work is to expand a biomechanical model-based deformable registration algorithm (Morfeus) to achieve accurate registration in the presence of significant anatomical changes. Six lung cancer patients previously treated with conventionally fractionated radiotherapy were retrospectively evaluated. Exhale CT scans were obtained at treatment planning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Additionally, the “Lung + ROI” option uses the same correlation coefficient as for the “Lung” setting, plus controlling contours to penalize contour variations between the registered images. One participant also used a custom version of the MORFEUS algorithm that incorporates boundary conditions on the lung vessel tree …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the “Lung + ROI” option uses the same correlation coefficient as for the “Lung” setting, plus controlling contours to penalize contour variations between the registered images. One participant also used a custom version of the MORFEUS algorithm that incorporates boundary conditions on the lung vessel tree …”
Section: Resultsmentioning
confidence: 99%
“…One participant also used a custom version of the MORFEUS algorithm that incorporates boundary conditions on the lung vessel tree. 38 Where the DIR cost function incorporated image similarity metrics, these were based on the intensity mean square error (MSE), cross correlation (CC), squared sum of tissue volume differences (SSTVD), or mutual information (MI). All of the DIR methods used some form of motion field regularization to avoid nonphysical folding of tissue (i.e., negative values of the Jacobian determinant), and a majority of DIR methods also used a "lung focus" (that is, where the DIR optimizer focuses on the lung voxels and/or lung contours).…”
Section: A Summary Of the Ctvi And Dir Motion Field Submissionsmentioning
confidence: 99%
“…This error measurement could be improved when applying this registration method to scans with improved slice thickness, in part because the reproducibility of manually selecting bifurcation points is dependent on slice thickness. Additionally, the modeling of the complex deformations observed in the liver might be improved by using corresponding vessel positions on the two CT scans as additional boundary conditions in the biomechanical model, as previously demonstrated in the lung [35]. However, this would rely on high-quality CT image contrast enabling visualization of vessels and the assumption of vessel preservation, which may not be a good assumption in the presence of large tumor response or cases of tumor induced thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The MDLM method could make robust probabilistic predictions on the occurrence of pulmonary vessels by feeding the learned voxel‐wise features to a logistic regression classifier. The pulmonary vasculature structures could provide abundant information about the vessels and reflect the motion of the lung accurately . We adopted the Harris‐Stephens algorithm to detect feature points on the vasculature probability maps.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our experimental experiences, we have observed that landmarks detected using SIFT or Harris corner key point detection methods may have positional uncertainties since these landmarks were detected as the local maximum points in the scale space and were not necessarily stable. On the other hand, the pulmonary vascular structures that have been used for lung image registrations were stable across the respiratory cycle . This was why we have chosen to detect feature points on the vasculature probability maps instead of the original CT images.…”
Section: Methodsmentioning
confidence: 99%